When and where did it happen? Systematic differences in recall of core and optional sentence information - Chromý, Jan; Vojvodić, Sonja (The quarterly journal of experimental psychology. 2006, 2024)
This article reports on four experiments aiming to examine immediate post-sentential recall of core sentence information (conveyed by direct objects), and optional/additional information (conveyed by temporal or locative adjuncts). Participants read simple and unambiguous Czech sentences such as Starší důchodce velmi pečlivě pročetl noviny v neděli v knihovně: "An older retiree read the newspaper very carefully on Sunday in the library." Sentences always appeared as a whole after pressing a space bar. Immediately after the sentence disappeared, an open-ended (free response) question was presented targeting either the direct object (e.g., newspaper), temporal adjunct (e.g., on Sunday), or locative adjunct (e.g., in the library). Altogether, it was found that the core information (conveyed by the direct object) was recalled almost perfectly, whereas additional information, conveyed by temporal and locative adjuncts, was recalled with significantly lower accuracy rates. Information structure also played a role: if the temporal or locative adjunct was focused, it was recalled better than if it was unfocused. The present article thus shows systematic differences in recall success for different pieces of information. These findings suggest the presence of selective attention mechanisms during early stages of sentence processing. Factors such as syntactic function or information structure influence the degree of attention to different pieces of information conveyed by a sentence. In turn, certain pieces of information may not be consciously accessible already after the sentence is processed.
Keywords: Comprehension; Mental Recall; Memory, Short-Term; Humans; lidé; Reading; krátkodobá paměť; Language; pochopení; jazyk (prostředek komunikace); čtení; rozpomínání